Theorem and Practicum:: Order, Value, Result, Interaction - Martin-Malikian, Elizabeth; Rizzuto, Anthony (ARCC Conference Repository, 2019)
The Thesis is the last major step toward graduation with a first professional degree, or Bachelor of Architecture (B.Arch.), which traditionally prepares students for practice. As a threshold between directed studios and independent thought, the Thesis provides an opportunity for the student to systematically explore a coherent line of investigation of issues relevant to the field of architecture. The Thesis is an intellectual position laid down or to be advanced. It is the first stage of the dialectic-discussion, that is, discussion and reasoning by dialogue as a method of intellectual investigation. An architectural thesis demands that a student take a position and have something to say that is relevant to the discursive field that it inhabits and/or its wider cultural context. In the field of architecture such intellectual positions have implications that result from a critique and re-examination of the role of architecture as a critical participant in the conditioning of public and private space. Thus, while an undergraduate architectural thesis originates in a determinate intellectual position, it culminates in a designed artifact, but rarely the artifact itself. This paper takes a step in characterizing architectural research, where the interaction of Theorem and Practicum is used not only as a guiding principle in the critical thinking process, but also as a springboard for constructive practices in the built realm. This particular reading is an inquiry into the importance and influence of interaction between Theorem and Practicum, as well as, the importance of which is observed through different modes of cross-pollination occurring in various aspects of architectural discourse and practice. This investigation is explored in four perspectives, labeled ‘order', ‘values', ‘results' and ‘interaction' are categorized according to their relationship to the investigation of Theorem and Practicum. Furthermore, these four attributes permeate and connect the diverse areas of research explored, which in combination provides an argument that rather than questioning: "is doing architecture doing research” as articulated by Jeremy Till, instead asks: "is doing research doing architecture”. Our aim is to expand the pedagogical field where the interaction of Theorem and Practicum is not an isolated act, but one of making.